Implementasi Sistem Akuaponik Organik Berbasis RAS (Recirculating Aquaponic System) oleh Green Street Farm dalam Mendukung Ketahanan Pangan Komunitas Perkotaan di Selangor, Malaysia - Arif Luqman; Iska Desmawati; Nabila Wildani Fathiatun Nida; Nicholas Willy Edrico; Dave Santoso; Muhammad Rizky Putra Wahyuana; Fiddodito Faizt Yanuarie; Yochellino Yuwen Purwanto; Mochamad Rooney Raffael Alrizqy; Maulina Habib Karenina Mustofa; Khansa Kineta Nirwasita; Michelle Tiffany Laowo; I’anah Rahman; Bintang Rahadi Putri (Universitas Nahdlatul Ulama Sidoarjo, 2026)
Rapid urbanization in urban areas of Southeast Asia, including Malaysia, has created significant pressure on conventional food security systems due to limited productive land and long supply chains. This community service activity aims to implement an organic aquaponic system based on RAS (Recirculating Aquaculture System) by Green Street Farm located in Selangor, Malaysia, to support food security in urban communities. The method used began with online coordination with the University of Malaya, followed by active team participation at Green Street Farm, Selangor, in aquaponic planting, aquaculture maintenance, basic system monitoring, fish feeding, and plant harvesting. The success of the activity was measured based on the products produced and marketed. The results showed that the system at Green Street Farm, Selangor, was able to produce various organic vegetable commodities, fresh fish, and various processed food products. All of these products were successfully marketed to the urban community around Selangor. This community service activity is declared successful because it has met the success indicators, namely the existence of products produced and marketed as tangible evidence of supporting urban food security. The advantage of this system is its ability to operate on limited land, but the drawback is that it requires regular monitoring. Future development opportunities include scaling up production and product diversification.